Laser-induced damage thresholds of ultrathin targets and their constraint on laser contrast in laser-driven ion acceleration experiments. (7th December 2020) - Wang, Dahui; Shou, Yinren; Wang, Pengjie; Liu, Jianbo; Mei, Zhusong; Cao, Zhengxuan; Zhang, Jianmin; Yang, Pengling; Feng, Guobin; Chen, Shiyou; Zhao, Yanying; Schreiber, Joerg; et al.
Abstract: Single-shot laser-induced damage threshold (LIDT) measurements of multi-type free-standing ultrathin foils were performed in a vacuum environment for 800 nm laser pulses with durations τ ranging from 50 fs to 200 ps. The results show that the laser damage threshold fluences (DTFs) of the ultrathin foils are significantly lower than those of corresponding bulk materials. Wide band gap dielectric targets such as SiN and formvar have larger DTFs than semiconductive and conductive targets by 1–3 orders of magnitude depending on the pulse duration. The damage mechanisms for different types of targets are studied. Based on the measurement, the constrain of the LIDTs on the laser contrast is discussed.